Estudo da evolução da escarpa do divisor hidrográfico Doce/Paraná em Minas Gerais - Leilane Cristina Goncalves Sobrinho (2012)
The Serra da Mantiqueira corresponds to a system that is comprised of mountains towards SW / NE and features high on the eastern edge of the South American continent. In the Zona da Mata, in the state of Minas Gerais, the Serra da Mantiqueira is characterized by a escarpment that separates four major river basins of southeastern Brazil: São Francisco river basin, Paraná river basin, Doce river basin and Paraiba do Sul river basin. In the hydrographic divide between the basins of the Paraná and Doce, the Serra da Mantiqueira form an escarpment that is a step in relief, dividing two plateaus: the Paraná Plateau and the Doce plateau. This is an erosive escarpment, in which the difference in the base level of the two basins is responsible for the existence of t he escarpment. The aim of this study is to investigate the evolution of the escarpment in the stretch between the towns of Carandaí and Barbacena, which is the divider between the hydrographic basins of the Paraná and Doce. The quantification of denudation rates by measuring isotopes of cosmogenic 10Be. The method of cosmogenic 10Be isotope covers a time span of 1.36 Ma, covering a significant part of the Quaternary. We selected eight sub-basins that drain the two slopes of the interfluve, five drain into the basin of the Doce and three draining into the Parana basin. Thus, the fluvial sediments were collected -medium sand and coarse - of the eight sub-basins for analysis of denudation rates. The results shows that the Doce catchments denudation rates has approximately 2.73 times higher than the denudation rates of the Parana catchments. The average rates of denudation for Serra da Mantiqueira are 14.73 m.Myr-1 for the part of the Sweet m.Myr-1 and 5.39 for strand of Parana. The highest intensity of erosion in the basin of Doce promotes the retreat of the escarpment in the Mountain range toward the Parana basin. This retraction of the escarpment is a function of piracy catchments processes occurring in the headwaters. The whole area comprises rocks of granite-gneiss complex and Ressaquinha Mantiqueira, which have equal resistance to erosion. Thus, the geology not affect the results of stripping rates. The altimetric gradient is a factor controlling the rate of denudation, and the average slope and amplitude of the basin. The data revealed that the higher the amplitude of the basin and slope, the greater the rate of denudation.